ANALISIS PERBANDINGAN IMBAL HASIL INVESTASI PRODUK REKSADANA SYARIAH BERIMBANG DAN REKSADANA ANGGREK DI DANAREKSA SEKURITAS CABANG MEDAN - Azizatur Rahmah (Universitas Islam Negeri Sumatera Utara, 2020)
Balanced Sharia Mutual Fund Product apply a cleaning or filtering process in the securities portfolio construction. The screening process carried out by removing the income obtained from activities thet are not in accordance with Islamic principles. This process raises doubts about the performance of this mutual fund. Investors also assume that the return on investment in Balanced Sharia Mutual Funds is not as large as the return on investment in the Orchid Mutual Fund. In this period, there is data that shows Balanced Sharia Mutual Funds experienced more profits than Anggrek Mutual Funds by 23 times. Even though during the research period Balanced Sharia Mutual Fund often provide higher invsetmen returns, Orchid Mutual Funds have also experienced the same thing. The results of calculations using the t-test method obtained t-count of 11.93. Thus t-stat>from t-table or 11.93>2.807. The t-stat value is obtained from the difference in the percentage of return on investment in the Orchid Mutual Fund minus the yeild for Balanced Sharia Mutual Funds of 171.77 divided by a deviation of 14.38. The conclusion of this study is that there are data that show Balanced Sharia Mutual Funds experience more benefits than Orchid Mutual Funds.